Answer:
<h2>SEE BELOW</h2>
Step-by-step explanation:
<h3>to understand this</h3><h3>you need to know about:</h3>
<h3>let's solve:</h3>
vertex:(h,k)
therefore
vertex:(-1,4)
axis of symmetry:x=h
therefore
axis of symmetry:x=-1
- to find the quadratic equation we need to figure out the vertex form of quadratic equation and then simply it to standard form i.e ax²+bx+c=0
vertex form of quadratic equation:
therefore
- y=a(x-(-1))²+4
- y=a(x+1)²+4
it's to notice that we don't know what a is
therefore we have to figure it out
the graph crosses y-asix at (0,3) coordinates
so,
3=a(0+1)²+4
simplify parentheses:
![3 = a(1 {)}^{2} + 4](https://tex.z-dn.net/?f=3%20%3D%20a%281%20%7B%29%7D%5E%7B2%7D%20%20%2B%204)
simplify exponent:
![3 = a + 4](https://tex.z-dn.net/?f=3%20%3D%20%20a%20%2B%204)
therefore
![a = - 1](https://tex.z-dn.net/?f=a%20%3D%20%20-%201)
our vertex form of quadratic equation is
let's simplify it to standard form
simplify square:
![y = - ( {x}^{2} + 2x + 1) + 4](https://tex.z-dn.net/?f=y%20%3D%20%20-%20%28%20%7Bx%7D%5E%7B2%7D%20%20%2B%202x%20%2B%201%29%20%20%2B%204)
simplify parentheses:
![y = - {x}^{2} - 2x - 1 + 4](https://tex.z-dn.net/?f=y%20%3D%20%20-%20%20%7Bx%7D%5E%7B2%7D%20%20-%202x%20-%201%20%2B%204)
simplify addition:
![y = - {x}^{2} - 2x + 3](https://tex.z-dn.net/?f=y%20%3D%20%20-%20%20%7Bx%7D%5E%7B2%7D%20%20-%202x%20%2B%203)
therefore our answer is D)y=-x²-2x+3
the domain of the function
![x\in \mathbb{R}](https://tex.z-dn.net/?f=x%5Cin%20%5Cmathbb%7BR%7D)
and the range of the function is
![y\leqslant 4](https://tex.z-dn.net/?f=y%5Cleqslant%204)
zeroes of the function:
![- {x}^{2} - 2x + 3 = 0](https://tex.z-dn.net/?f=%20-%20%20%7Bx%7D%5E%7B2%7D%20%20-%202x%20%2B%203%20%3D%200)
![\sf divide \: both \: sides \: by \: - 1](https://tex.z-dn.net/?f=%20%5Csf%20divide%20%5C%3A%20both%20%5C%3A%20sides%20%5C%3A%20by%20%5C%3A%20%20-%201)
![{x}^{2} + 2x - 3 = 0](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20%2B%202x%20-%203%20%3D%200)
![\implies \: {x}^{2} + 3x - x + 3 = 0](https://tex.z-dn.net/?f=%20%5Cimplies%20%5C%3A%20%20%7Bx%7D%5E%7B2%7D%20%2B%20%20%203x%20%20-%20x%20%20%2B%20%203%20%3D%200)
factor out x and -1 respectively:
![\sf \implies \: x(x + 3) - 1(x + 3 )= 0](https://tex.z-dn.net/?f=%20%5Csf%20%5Cimplies%20%5C%3A%20x%28x%20%2B%203%29%20%20%20-%201%28x%20%20%2B%203%20%29%3D%200)
group:
![\implies \: (x - 1)(x + 3) = 0](https://tex.z-dn.net/?f=%20%5Cimplies%20%5C%3A%20%28x%20-%201%29%28x%20%2B%203%29%20%3D%200)
therefore
![\begin{cases} x_{1} = 1 \\ x_{2} = - 3\end{cases}](https://tex.z-dn.net/?f=%20%20%5Cbegin%7Bcases%7D%20x_%7B1%7D%20%3D%201%20%5C%5C%20%20x_%7B2%7D%20%20%3D%20%20-%203%5Cend%7Bcases%7D)